Effects of decreasing maternal separation of under 6-month old infants directly before and after surgery on allostatic load and outcomes : a randomised control trail [i.e. trial] - Ssenyonga, Lydia V N (Division of Nursing and Midwifery, 2014)
Includes abstract.